Penerapan Bioinformatika dalam Studi Genomik Berbasis Proyek di SMA pada Era Digital dan Bioteknologi - Tasrari Qolbi Nur Kholis; Reswara Fawwaz Achmad; Aura Rahmadhani; Winda Amira Rafifah; Nurina Tahta Afwi Maulina; Siti Nur Jannah (Direktorat Pengabdian kepada Masyarakat, 2026)
Bioinformatics constitutes a significant branch of biotechnology that integrates computational methodologies into its applications. This discipline holds substantial promise for the future, particularly within the healthcare sector, where it plays a pivotal role in genomic research, including the identification of novel therapeutic candidates. Despite its growing relevance, the field is still relatively unfamiliar to many stakeholders and the development of bioinformatics remains constrained by limited human resources. This activity is therefore intended to enhance awareness of bioinformatics and to increase the number of individuals equipped with the skills required to engage with this field. The program targets secondary level students and implements a project-based learning (PBL) approach, evaluated through both qualitative and quantitative measures. The qualitative methods are used to assess students’ capabilities in completing their project-based learning tasks. The quantitative methods are used to assess the effectiveness of the instructional material delivery by comparing pretest scores with posttest scores. Among 30 students, the pretest results showed an average score of 79.5, while the posttest results showed an average score of 91.2. This indicates an improvement in scores before and after the instruction. The combined evaluation demonstrates that students are capable of comprehending the subject matter and completing group based project assignments in an effective and timely manner. It is anticipated that, moving forward, a growing number of learners will acquire competency in bioinformatics, enabling its application to real world challenges and fostering the development of high impact scientific and technological innovations.